Understanding the differentiation, expansion, recruitment and suppressive activities of myeloid-derived suppressor cells in cancers - Lim, Hui Xuan *; Kim, Tae Sung; Poh, Chit Laa * (MDPI, 2020)
There has been a great interest in myeloid-derived suppressor cells (MDSCs) due to their biological functions in tumor-mediated immune escape by suppressing antitumor immune responses. These cells arise from altered myelopoiesis in response to the tumor-derived factors. The most recognized function of MDSCs is suppressing anti-tumor immune responses by impairing T cell functions, and these cells are the most important players in cancer dissemination and metastasis. Therefore, understanding the factors and the mechanism of MDSC differentiation, expansion, and recruitment into the tumor microenvironment can lead to its control. However, most of the studies only defined MDSCs with no further characterization of granulocytic and monocytic subsets. In this review, we discuss the mechanisms by which specific MDSC subsets contribute to cancers. A better understanding of MDSC subset development and the specific molecular mechanism is needed to identify treatment targets. The understanding of the specific molecular mechanisms responsible for MDSC accumulation would enable more precise therapeutic targeting of these cells.